Attenuation of access to internal states in high obsessive-compulsive individuals might increase susceptibility to false feedback: Evidence from a visuo-motor hand-reaching task. (December 2019) - Ezrati, Or; Friedman, Jason; Dar, Reuven
Abstract: Background and objectives: The Seeking Proxies for Internal States (SPIS) model of obsessive-compulsive disorder (OCD) posits that obsessive-compulsive (OC) individuals have attenuated access to their internal states. Hence, they seek and rely on proxies, or discernible substitutes for these internal states. In previous studies, participants with high OC tendencies and OCD patients, compared to controls, showed increased reliance on external proxies and were more influenced by false feedback when judging their internal states. This study is the first to examine the effects of false feedback on performance of hand movements in participants with high and low OC tendencies. Method: Thirty-four participants with high OC tendencies and 34 participants with low OC tendencies were asked to perform accurate hand reaches without visual feedback in two separate sessions of a computerized hand-reaching task: once after valid feedback training of their hand location and once with false-rotated feedback. We assessed the accuracy and directional adaptation of participants' reaches. Results: As predicted, high OC participants evidenced a larger decrease in their hand positioning accuracy after training with false feedback compared to low OC participants. Limitations: The generalization of our findings to OCD requires replication with a clinical sample. Conclusions: These results suggest that in addition to self-perceptions, motor performance of OC individuals is prone to be overly influenced by false feedback, possibly due to attenuated access to proprioceptive cues. These findings may be particularly relevant to understanding the distorted sense of agency in OCD. Highlights: Influence of false feedback in low vs. high obsessive compulsive (OC) participants. Hand reaching accuracy was tested after training with valid and rotated feedback. Reaching accuracy of High OC had larger decrease after training with false feedback. Attenuated access to internal states in OC individuals may explain findings.